REKONSTRUKSI LITERATUR SISTEM POLITIK DAN NEGARA IBNU TAIMIYAH - Saende, Zubair Rahman; Sultan, Lomba; Asni (ISTIQRA: Jurnal Hasil Penelitian, 2023)
This research aims to explain Ibn Taymiyah's political thought in the history of Islamic politics and its implications for current Islamic political thought. especially the social setting that forms the basis of Ibn Taymiyah's thoughts about the political system and state offered by Ibn Taimiyah, and whether his theory is still relevant to current socio-political conditions. The method used in this research is a qualitative method with a type of library research, the approach used is historical-critical-philosophical, then the data sources in the research are primary and secondary data. Based on the data that has been collected and analyzed, the conclusions of this research show that Ibn Taymiyah with his courage abolished/rejected the leadership system of the caliphate and imamate, with his thesis that the regime upheld by the prophet was the nubuwwah regime and not the imamate, while the new imamate existed after the prophet died. shows that he has revolutionary and reformist ideas. He didn't want people to just be objects in a state, but he wanted people to be subjects of a state. For Ibnu Taymiyah, the mechanism/system for appointing the head of state is not very important, what is important is that the person occupying the position must be truly trustworthy and fair. Ibn Taimiyah required two things for a head of state, namely having the qualifications of strength (al-quwwah) and integrity (al-amanat). Strength and integrity are obtained through the mubaya'ah (oath of allegiance) given by the ahl al-Syawkah.